Dendrobium annulatum (Orchidaceae: Epidendroideae), a new species of Dendrobium section Grastidium from Indonesian New Guinea - Juswara, Lina S.; Schuiteman, André; Champion, Jeffrey (Phytotaxa, 2019)
The second largest genus of Orchidaceae, Dendrobium Swartz (1799: 82), has close to 1600 accepted species names (Govaerts et al. 2019). Indonesia is particularly rich in species of Dendrobium, with, for example, 114 and 53 species recorded from Sumatra and Java, respectively (Comber 1990, 2003). However, this pales in comparison to New Guinea, where 612 species of Dendrobium are known to occur, 86% of which are endemic. About 299 Dendrobium species are known from Indonesian New Guinea as opposed to 439 from Papua New Guinea, perhaps reflecting the lower collecting density in Indonesian New Guinea rather than actual lower species diversity (Schuiteman, unpublished).